Experimental Design of Vortex Assisted Switchable Solvent Homogeneous Liquid-Liquid Microextraction for Simultaneous Determination of Four Pesticides in Wastewater - Tisli, Busra; Chormey, Dotse Selali; Ayyildiz, Merve Firat; Bakirdere, Sezgin (OXFORD UNIV PRESS INC, 2020)
Background: Pesticides are chemicals used mainly to protect plant crops in order to increase their production efficiency and quality. Objective: Switchable-solvent homogeneous liquid-liquid microextraction was optimized using a Box-Behnken experimental design and validated on a gas chromatography mass spectrometry system for the determination of analytes. Method: The significance of independent variables (switchable solvent volume, sodium hydroxide volume, and vortex period) and their interactions were evaluated by analysis of variance at 95% confidence limits (alpha = 0.05). Results: The LOD and LOQ ranges of the analytes were found to be 0.42-1.90 mu g/L and 1.36-6.33 mu g/L, respectively. Percentage recovery results were found to be in the range of 87-113% in spiking experiments. Conclusions: A simple, efficient, and accurate analytical method was developed for the simultaneous determination of the selected pesticides. Highlights: Matrix matching was used to enhance quantification accuracy for real samples. Highlights: Matrix matching was used to enhance quantification accuracy for real samples.
Keywords: DEEP EUTECTIC SOLVENT; SINGLE-DROP MICROEXTRACTION; PHASE MICROEXTRACTION; GAS-CHROMATOGRAPHY; ORGANOPHOSPHORUS PESTICIDES; ORGANOCHLORINE PESTICIDES; EXTRACTION; SAMPLES; PRECONCENTRATION; RESIDUES; Chemistry; Food Science & Technology